Vulnerability of Women and Climate Change in Coastal Bangladesh - Zahan, Nasrin (European Scientific Journal, ESJ, 2022)
This paper focuses on providing a comprehensive scenario of women’s vulnerabilities based on the effects of climate change in Bangladesh. To address the problem, this study focuses on the nature of suffering and how they have tried to mitigate it. This study followed the purposive sampling method of a total of sixty respondents from the Satkhira district. Primary data were collected through a structured questionnaire, survey, and observation method. Besides these, secondary sources of national and international levels have been used in this study. This study found that sanitation problems of women and young girls as well as the lack of pure drinking water are common during the disaster time in the study area. In the context of a patriarchal society like Bangladesh, women are compelled to be submissive and obey the decision of male members due to prevalent social and cultural norms and conditions. As a result, most of the time, even when problem arise, women do not take any decision about whether they would stay at their home or seek shelter. The study uses an exploratory approach, and it will provide an insight into different sorts of sufferings as well as the detrimental effects of such natural disasters. It will also provide a better understanding and intensity of the problem. Although innumerable studies of climate change and its effects have been published, underlying scenarios are not properly focused on. Therefore, it would obviously help for further study as well as policymaking.